Simulation study of improving oil recovery by polymer flooding in a Malaysian reservoir - Hammuda Aluhwal, Omar Kalifa (2008)
This research is a simulation study to improve oil recovery using waterflooding and polymer flooding techniques based on data obtained from the Perdana oilfield in Malaysia and the Brillig reservoir as described in Eclipse 2000. There was no published report on polymer flooding project or polymer flooding simulation work that has been carried out for the Perdana oilfield. These two simulation studies have illustrated the feasibility of polymer flooding and provided the technical knowledge that can be used to study other techniques of improved oil recovery (IOR) to be implemented in Malaysian oilfields. Use of polymer increases water viscosity which controls water mobility thus improving the sweep efficiency. The simulations were carried out using the black oil model. In the simulation, factors such as polymer shear thinning effect, adsorption, concentration, permeability reduction, and fluid viscosity have been taken into account when constructing the mathematical model. For the Perdana reservoir, the polymer slug size was 0.624 PV, polymer concentration was 2500 ppm, oil recovery was 48%, and the incremental oil recovery was about 11%. For Brillig reservoir, the polymer slug size was 1.11 PV, polymer concentration was 2000 ppm, oil recovery was 45%, and the incremental oil recovery was about 8%. The waterflooding and polymer flooding costs were also studied for both methods in the Perdana reservoir. The polymer flooding project in this study has shown a better outcome compared to waterflooding project. The total production costs for a single barrel via polymer flooding and waterflooding were US$9.57 and US$5.68 respectively. Following that, the forecasted net profits of polymer flooding and water flooding for the Perdana oil field were US$2.04 billion and US$1.65 billion respectively, and the profit from the polymer flooding project over waterflooding project was US$390 million.